2019
DOI: 10.1111/febs.15089
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Cannabis sativa olivetol‐producing enzyme reveals cyclization plasticity in type III polyketide synthases

Abstract: In the native pathway to therapeutic cannabinoid biosynthesis in Cannabis sativa, the three‐step production of a key intermediate, olivetolic acid, is catalysed by the enzymes tetraketide synthase (TKS; linear tetraketide intermediate production in two stages) and olivetolic acid cyclase (OAC; final C2 → C7 aldol condensation). In the absence of OAC, a nonenzymatic C2 → C7 decarboxylative aldol condensation of the tetraketide intermediate occurs forming olivetol. TKS is a type III polyketide synthase, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…2a) (Gagne et al 2012;Tan et al 2018;Kearsey et al 2019). Kearsey et al (2019) also confirmed that, in the absence of OAC, a nonenzymatic C2 → C7 decarboxylative aldol condensation of the tetraketide intermediate occurs forming olivetol instead of OLA ( Fig. 2a).…”
Section: Cannabinoids Are Synthesized Through a Common Pathway In Trisupporting
confidence: 61%
See 3 more Smart Citations
“…2a) (Gagne et al 2012;Tan et al 2018;Kearsey et al 2019). Kearsey et al (2019) also confirmed that, in the absence of OAC, a nonenzymatic C2 → C7 decarboxylative aldol condensation of the tetraketide intermediate occurs forming olivetol instead of OLA ( Fig. 2a).…”
Section: Cannabinoids Are Synthesized Through a Common Pathway In Trisupporting
confidence: 61%
“…This conundrum, OLA cannot be prepared in vitro, but the in vitro product, olivetol, is not observed in vivo, has since been resolved by evidence that the process requires olivetolic acid cyclase (OAC), to conduct the intramolecular C2 → C7 aldol condensation without decarboxylation ( Fig. 2a) (Gagne et al 2012;Tan et al 2018;Kearsey et al 2019). Kearsey et al (2019) also confirmed that, in the absence of OAC, a nonenzymatic C2 → C7 decarboxylative aldol condensation of the tetraketide intermediate occurs forming olivetol instead of OLA ( Fig.…”
Section: Cannabinoids Are Synthesized Through a Common Pathway In Trimentioning
confidence: 95%
See 2 more Smart Citations
“…For MALDI TOF/TOF, the peptides were eluted with 2-10 µl of 0.1% TFA in 95% ACN and then coated onto MALDI plate with matrix. For LC-MS/MS, peptides were eluted with 2-10 µl of 0.1% formic acid in 95% ACN and then dispensed into auto-sampler vial 18 . MS/MS spectra were searched against NCBInr database using the parameters as mentioned in Table 1.…”
Section: Methodsmentioning
confidence: 99%